2019
DOI: 10.1103/physrevlett.123.133602
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Shaping and Reshaping of Single-Photon Temporal Wave Functions

Abstract: Thorough control of the optical mode of a single photon is essential for quantum information applications. We present a comprehensive experimental and theoretical study of a light-matter interface based on cavity quantum electrodynamics. We identify key parameters like the phases of the involved light fields and demonstrate absolute, flexible, and accurate control of the timedependent complex-valued wave function of a single photon over several orders of magnitude. This capability will be an important tool for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 39 publications
(60 reference statements)
0
52
0
Order By: Relevance
“…We note that the generation rate will eventually be limited by the inverse of the wavepacket's temporal length, which can be optimized by exploiting the Purcell effect or selecting a different kind of quantum dots. We also note that, in contrast to the wavepacket engineering achieved with single ions, atomic ensembles, or nonlinear crystals, [ 17–24,30–32,36–43,61–63 ] the wavepacket shaping utilized in our work manipulates the temporal envelope but not the wavefunction of the single photons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the generation rate will eventually be limited by the inverse of the wavepacket's temporal length, which can be optimized by exploiting the Purcell effect or selecting a different kind of quantum dots. We also note that, in contrast to the wavepacket engineering achieved with single ions, atomic ensembles, or nonlinear crystals, [ 17–24,30–32,36–43,61–63 ] the wavepacket shaping utilized in our work manipulates the temporal envelope but not the wavefunction of the single photons.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] To manipulate the quantum wavepackets, the modulation of single and entangled photons by modulators has emerged as a powerful and straightforward quantum optics tool. Like many other methods that shape the laser pulses pumping the single atom, ion, or quantum dot in the single‐ or entangled‐ photon emission, [ 17–23 ] the temporally long wavepacket of the single or entangled photons plays an indispensable role. The electro‐optic modulation of a single‐photon wavepacket was first demonstrated by the Harris group at Stanford University.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such a fast control over the near-field interactions will expand existing functionalities of plasmonic nanodevices integrating graphene waveguides and cavities 28 , 29 , 36 38 . It enables the control of the waveform of photons and plasmons emitted into a guided mode 21 , 39 , which is a required capability for distributed quantum systems. It furthermore facilitates the connection of optical transistors 40 , 41 based on quantum emitters in integrated plasmonic circuits, with the possibility to attenuate or amplify the plasmon emission by means of a gate voltage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have illustrated the method on an experimental case and confirmed that it is a powerful way to reconstruct even a sophisticated shape. Hence, we believe that this will facilitate the implementation of the presented technique beyond the continuous variables community and make this technique a standard routine in quantum optics laboratories [21].…”
Section: Data Processing Reconstructionmentioning
confidence: 94%